Household cost of chronic kidney disease care among patients presenting at Komfo Anokye Teaching Hospital, Ghana - Kumah, Emmanuel; Agyei-Baffour, Peter; Kofi Acheampong, Michael; Anarfi Boateng, Kwabena; Larbie, Deborah; Kwasi Afriyie, Emmanuel; Sayi, Daniel (African Journal of Nephrology, 2022)
Background: Chronic kidney disease (CKD) has a major effect on global health, both as a direct cause of morbidity and mortality and as a risk factor for cardiovascular disease. This study was carried out to determine the household cost of CKD care among patients receiving treatment at a tertiary healthcare facility in Ghana. Methods: This was a cross-sectional study conducted over a period of three months. The estimated household cost of CKD care was made up of direct and indirect cost of treating the condition. The direct cost was divided into direct medical cost and direct non-medical cost. The direct medical cost included cost of medication, outpatient consultations, cost of dialysis, diagnostic investigations (including laboratory investigations), and ultrasound and computed tomography requests. The direct non-medical cost included cost of feeding and transportation. The indirect cost was based on the total time lost to productivity. Results: A total of 224 patients were included in the study. The mean ±SD age of the patients was 49.62 ±15.37 years. The overall average monthly cost of CKD care for the 224 patients was GH₵ (US$) 1,121.42 (198.63), making up of 87.70% direct cost and 12.30% indirect cost. The cost incurred by CKD patients on dialysis was significantly higher and almost four times higher than that of the end stage non-dialysis CKD patients.